Treatment of Masticatory Muscle Pain with Acupuncture: Is It Necessary to Associate with Occlusal Splints? - Crischina Branco Marques Sant'Anna; Fernanda Pereira de Caxias; Paulo Renato Junqueira Zuim; Marcella Santos Januzzi; Emily Viviane Freitas da Silva; Karina Helga Leal Turcio (Medical Association of Pharmacopuncture Institute, 2021)
Background : Temporomandibular disorders (TMDs) are treated by different modalities including splints, physiotherapy, and acupuncture. Although all of these offer evidencebased benefits to the patients, avoiding overtreatment is of paramount importance. Objectives: To assess the effectiveness of muscle pain treatment with acupuncture combined with or without occlusal splints. Methods : Recruited patients were allocated to G1 (acupuncture) and G2 (acupuncture and occlusal splint) groups and treated in four consecutive weekly sessions (P1, P2, P3, and P4). The reported pain (RP) and the pressure pain threshold (PPT) of the masseter and temporalis muscles were assessed before and after each session. Results : RP decreased after each session in G1, except at P4. In G2, the RP decreased only after the first session, and the PPT did not vary. Conclusion : The assessed treatments did not influence the PPT levels of the masseter and anterior temporalis muscles in patients with temporomandibular disorders. Our findings suggest that occlusal splints may not be mandatory along with the acupuncture treatment.